2011
DOI: 10.4028/www.scientific.net/amr.396-398.140
|View full text |Cite
|
Sign up to set email alerts
|

OD-Characterization of the Symmetric Group S<sub>28</sub>

Abstract: It is proved that the symmetric group S28 is characterized by its order and degree pattern. In fact, S28 is 3-fold OD-characterizable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a series of articles ( Ref.to [2]- [17]), it was shown that many finite almost simple groups are OD-characterizable [see [2] Definition 1.1 and 1.2]. For convenience, we point out some of these results in the following proposition 1.…”
Section: Introductionmentioning
confidence: 95%
“…In a series of articles ( Ref.to [2]- [17]), it was shown that many finite almost simple groups are OD-characterizable [see [2] Definition 1.1 and 1.2]. For convenience, we point out some of these results in the following proposition 1.…”
Section: Introductionmentioning
confidence: 95%